2012
DOI: 10.1038/am.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Realizing a SnO2-based ultraviolet light-emitting diode via breaking the dipole-forbidden rule

Abstract: Although many oxide semiconductors possess wide bandgaps in the ultraviolet (UV) regime, currently the majority of them cannot efficiently emit UV light because the band-edge optical transition is forbidden in a perfect lattice as a result of the symmetry of the band-edge states. This quantum mechanical rule severely constrains the optical applications of wide-bandgap oxides, which is also the reason why so few oxides enjoy the success of ZnO. Here, using SnO 2 as an example, we demonstrate both theoretically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 47 publications
6
105
1
Order By: Relevance
“…• C which is accompanied by a gradual suppression of the photoluminescence (PL) peak at 2.25 eV related to surface states of SnO 2 , and the emergence of a peak at 3.65 eV corresponding to band edge emission from electrostatically defined SnO 2 quantum dots in accordance with Li et al 28 These Cu 2 SnS 3 /SnO 2 NW assemblies have very low resistances of ≈100 Ω similar to that of ITO NWs. On the other hand, we observe the existence of the cubic bixbyite crystal structure of In 2 O 3 and chalcopyrite CuInS 2 obtained from Cu/Sn:In 2 O 3 NWs under H 2 S between 100 and 500…”
supporting
confidence: 75%
“…• C which is accompanied by a gradual suppression of the photoluminescence (PL) peak at 2.25 eV related to surface states of SnO 2 , and the emergence of a peak at 3.65 eV corresponding to band edge emission from electrostatically defined SnO 2 quantum dots in accordance with Li et al 28 These Cu 2 SnS 3 /SnO 2 NW assemblies have very low resistances of ≈100 Ω similar to that of ITO NWs. On the other hand, we observe the existence of the cubic bixbyite crystal structure of In 2 O 3 and chalcopyrite CuInS 2 obtained from Cu/Sn:In 2 O 3 NWs under H 2 S between 100 and 500…”
supporting
confidence: 75%
“…Up to now, the photoluminescence mechanism of SnO 2 is still not clear. [43][44][45][46][47][48][49] It is believed that the surface oxygen vacancies defect states can induce direct gap transitions and generate possible photoluminescence. [43][44][45] Recently, Li et al found that that the SnO 2 nanostructures can break the dipole-forbidden rule and realize UV luminescence.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45] Recently, Li et al found that that the SnO 2 nanostructures can break the dipole-forbidden rule and realize UV luminescence. 46 The HRTEM image of an individual SnO 2 nanowire shown in Figure 1(b) indicates the existence of surface defect states, which can induce the low symmetry of the surface structure and realize the effective UV emission from the SnO 2 nanowires. 46 Here, the UV emission band at 361 nm is attributed to band edge recombination of the photogenerated carriers, which may be originated from the conduction band to acceptors and neutral-donar-bound excitons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanowire dimensions were too large to construct models simulating modified surface band structures. 51 Thus, the calculations focused on the effect of defects on magnetic order. Three occupied configurations: (i) two NN Sn atoms, (ii) two NN Zn atoms and (iii) NN Sn and Zn atoms, were replaced by two Mn atoms.…”
Section: Resultsmentioning
confidence: 99%